Hubungan Disfagia Dengan Kejadian Gangguan Elektrolit Pada Pasien Stroke Iskemik Yang Dirawat Di Bangsal Saraf RSUD Arifin Achmad Provinsi Riau Tahun 2023 - Sukiandra, Riki (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Ischemic stroke is the most common type of stroke according to the South East Asian Medical Information Center (SEAMIC). The prevalence of stroke in Riau is 8.3%, which has increased from 2013. One of the symptoms of ischemic stroke is dysphagia which is defined as difficulty swallowing, which means difficulty passing food from the mouth to the stomach. This symptom is of concern because it is a common cause of dehydration resulting in electrolyte imbalance, stroke associated pneumonia (SAP) which can increase mortality rates. The need for early detection of dysphagia can reduce the incidence of electrolyte disorders. Aim: To determine the relationship between dysphagia and the incidence of electrolyte imbalance in ischemic stroke patients treated in the neurology ward of Arifin Achmad Regional Hospital, Riau Province. Methods: This research is an analytical research with a cross sectional method. The research will be carried out in the neurological ward of Arifin Achmad Regional Hospital, Riau Province from August – November 2023. Results: In this study, it was found that 42.5% of ischemic stroke patients experienced dysphagia with the characteristics of the majority being 51-60 years old (41.2%) male (58.8%) with a frequency of first stroke attacks (52.9%) and the majority had multiple risk factors (70.6%). The majority of electrolyte levels in dysphagia patients have low electrolyte levels. The most common lesion locations in dysphagia patients were subcortical and combined (35.3%). There was a significant relationship between dysphagia and the incidence of electrolyte disturbances (p=0.000). Discussion: Lack of fluid intake that does not reach optimal needs can be a risk of dehydration which can lead to electrolyte disorders. Dysphagia directly interferes with the ability to eat and drink so that intake is not strong. This can affect water and electrolyte balance Keywords: dysphagia, electrolyte imbalance, ischemic stroke